Using Story-Based Interventions to Improve Episodic Memory in Autism Spectrum Disorder - Hutchins, Tiffany L.; Prelock, Patricia A. (Seminars in Speech and Language, 2018)
Episodic memory (EM) and scene construction are critical for organizing and understanding personally experienced events and for developing several aspects of social cognition including self-concept, identity, introspection, future thinking, counterfactual reasoning, theory of mind, self-regulation, flexible problem-solving, and socially adaptive behavior. This article challenges the reader to think differently about EM in children with autism spectrum disorder (ASD), as we expand our understanding of autobiographical memory that requires an ability to travel back in time and re-experience an event. The role of EM in cognitive and behavioral functioning for children with and without ASD is described. The value of story-based interventions such as Social Stories and Comic Strip Conversations for supporting EM is discussed with adaptations recommended to ensure a rich personal recall of an event. By focusing on EM and scene construction, there is potential for increasing the potency of story-based interventions for achieving maximum therapeutic impact.
Keywords: Social cognition; social stories; episodic memory; autobiographical memory; elaborative reminiscing